Gene Expression of Fresh and Frozen/Thawed Canine Embryos - Guaitolini, C Renato de Freitas; Maziero, R. R.D.; Castilho, A Cesar de Souza; Derussi, A. A.P.; Volpato, R. [UNESP]; Ackermann, C. L. [UNESP]; Matsubara, L. M. [UNESP]; Lopes, M. D. [UNESP] (My University, 2020)
BACKGROUND: Canine embryo cryopreservation and subsequent transfer are relevant in the use of reproductive technologies. OBJECTIVE: The purpose of this study is the identification and quantification of the gene expression BAX and Bcl2, AQP3, Na+/K+ ATPase alpha-1 and beta-1 and LIFr in canine embryos obtained in vivo and after freezing. MATERIALS AND METHODS: For the collection of embryos, the bitches were identified at pro-estrous until the detection of 80-90% superficial cells. After that, they were artificially inseminated with fresh semen. The embryos were collected after ovariohysterectomy. RNA was extracted and amplified, and embryos were randomly distributed into fresh (Fr) and frozen/thawed (Ft) groups. RESULTS: Eighteen blastocysts were collected from three bitches. Genes BAX, AQP3 and LIFr did not differ among the studied groups. CONCLUSION: We suggest, through these results, that the genes BAX, Bcl2, AQP3, Na + / K + ATPase alpha-1 and beta-1 and LIFr were expressed in canine blastocysts collected in vivo and after slow freezing cryopreservation.